The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00170-019-04280-2
|View full text |Cite
|
Sign up to set email alerts
|

Influences of up-milling and down-milling on surface integrity and fatigue strength of X160CrMoV12 steel

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This is an author-deposited version published in: https://sam.ensam.eu Handle ID: .http://hdl.handle.net/10985/18458 To cite this version :Adnen LAAMOURI, Farhat GHANEM, Chedly BRAHAM, Habib SIDHOM -Influences of up-milling and down-milling on surface integrity and fatigue strength of X160CrMoV12 steel Abstract This paper aims to compare the influences of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…On the contrary, the surface residual stress and its influence layer depth under horizontal upward were deeper than horizontal upward. It is commonly known that surface integrity plays an important role in fatigue life, so Laamouri et al 25 evaluated the influence of the milling path on surface integrity and fatigue strength of X160CrMoV12. The surface showed tensile residual stress, and metal wrinkles and short microcracks occurred in up milling.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the surface residual stress and its influence layer depth under horizontal upward were deeper than horizontal upward. It is commonly known that surface integrity plays an important role in fatigue life, so Laamouri et al 25 evaluated the influence of the milling path on surface integrity and fatigue strength of X160CrMoV12. The surface showed tensile residual stress, and metal wrinkles and short microcracks occurred in up milling.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion is believed to compromise the true geometry and sharpness of the cutting edge, thus leading to generation of a rougher surface. The superiority of down-milling regarding work surface finish was also reported for the milling of a tool steel [26]. It is quite surprising to see micro-lubrication yielding better surface finish than the two cryogenic coolants.…”
Section: Work Surface Roughnessmentioning
confidence: 64%
“…Mia et al reported that the use of dual jets of LN 2 is an excellent way to reduce energy consumption and working temperature, as well as to improve work surface quality [15]. In another experimental study, it was reported that the use of liquid CO 2 at a temperature of −79.5 • C in cutting of a nickel-chromium alloy could reduce average surface roughness by [42][43][44][45][46][47][24][25][26][27][16][17][18][19][20][21] wet, and MQL cutting, respectively [16]. Furthermore, the cryogenic cooling was also found to increase the compressive stresses on the surface and decrease the flank wear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvements in the mechanical properties of the SRM with CCC by adding fillers or reinforcing additives, such as wollastonite, glass fibers, carbon fibers, glass sphere, molybdenum disulfide [ 66 , 67 , 68 , 69 ], zirconia [ 70 , 71 , 72 ], silica sand, or silicon nitride [ 73 , 74 , 75 ] into the SRB is also an important research issue. In addition, the internal surface of CCC has high surface roughness [ 76 , 77 , 78 ] and result in reduction in mold life due to stress concentration [ 79 , 80 , 81 , 82 ]. Thus, surface improvement of the CCC by abrasive flow machining [ 83 ], electrochemical polishing [ 84 ], chemical polishing [ 85 ], laser polishing [ 86 ], ultrasonic cavitation abrasive finishing [ 87 ], or abrasive blasting [ 88 ] is also an important research topic.…”
Section: Resultsmentioning
confidence: 99%